P280 Extended Clinical Experience With Pirfenidone During A Named Patient Programme For Idiopathic Pulmonary Fibrosis (ipf): Interim Results. (10th November 2014) - Parfrey, H; Chaudhuri, N; Gibbons, MA; Anning, L; Balkin, M; Cooper, S; Dew, R; Maher, TM
Abstract : Introduction and objectives: From September 2011 to May 2013, pirfenidone was available in the UK in a named patient programme (NPP). We present results from an extension to a previous real-world study (Parfrey et al . Abstract S98, BTS Winter Conference 2012) now including longer follow-up and all patients enrolled in the pirfenidone NPP from 4 centres. Methods: Four centre, retrospective, cohort review of patient outcomes in the 24 months following pirfenidone initiation in the NPP. Discontinuation data were separately collected for all patients prescribed pirfenidone at the Brompton between Sept 2011 and May 2014. Results: Two hundred and eighteen eligible patients have been identified. Demographic data have been collected for 124 patients (78% male) and outcome data at 12 months from 58 patients. Mean (±S. D.) age at diagnosis was 67.1(± 8.1) years. Mean time from diagnosis to pirfenidone initiation was 27.7(± 30.6) months. At pirfenidone initiation, mean FVC was 69.3(±18.9)% predicted (with 27 (22.0%) patients having FVC >80% predicted); DLco was 40.3(± 13.8)% predicted. Following a 14-day titration period, 53 (93%) patients were receiving the recommended dose of 2403 mg/day pirfenidone. At 6 and 12 months; 47 (81%) and 44 (76%) patients continued to receive pirfenidone. 187 patients have been prescribed pirfenidone at the Brompton since Sept 2011. At 10 months following initiation 18.5% of these have discontinued pirfenidone with no further discontinuations beyond this time. For patients in the NPP with available paired baseline and 6 or 12 month FVC, mean decline in FVC% predicted over first 6 months of pirfenidone treatment was 3.2(± 7.9)%; over first 12 months 1.6(±12.0)%. One patient's FVC% predicted declined >10% in the first 12 months of treatment. Mean decline in DLco% predicted over first 6 months from pirfenidone initiation was 9.1(± 14.7)%; over first 12 months' treatment, 7.0(± 17.2)%. Conclusions: The high proportion of patients remaining on pirfenidone at 12 months suggests it is well tolerated and any tolerability issues tend to occur early in treatment. Lung function is largely preserved at 12 months following pirfenidone initiation. Longer-term observation of lung function and clinical outcomes will continue to determine the real-world benefits of pirfenidone.